Analisis Struktur dan Nilai Tambah Pada Rantai Pasok Beras di Kabupaten Aceh Timur - Muammar Aris Munandar; Irfan Irfan; Rachman Jaya (Agricultural Faculty, 2020)
The development of the agricultural sector is faced with the challenges in increasing of production and farmers' welfare. In addition to technical problems, the factor of supply chain must be considered properly because it is related to other social problems. This study discussed the structure of the rice supply chain in East Aceh District. The added value wich was gained by rice refineries in processing of paddy into rice was also examined by using Hayami method. The results showed that the rice supply chain in East Aceh involved several parties, namely farmers, collecto rs, rice refineries, large traders (districts), and retailers in and outside of East Aceh District as well as consumers as the last link. The added value generated from the processing of paddy into rice , bran and groats as a whole was able to provide a positive added value for rice refineries in East Aceh. The value of rice processing output was Rp. 6,304.5/kg. From the results of this output value, the rice refineries can produce an added value of Rp. 829 kg with a ratio of 13.14% in one processing period.